Using Geographical Information Systems for Decision Making: Extending Cognitive Fit Theory to Map-Based Presentations - Dennis, Alan R.; Carte, Traci A. (Information Systems Research, 1998)
As the use of Geographical Information Systems (GIS) by business becomes more common, we need to better understand when these systems are and are not useful. This research uses a laboratory experiment to extend cognitive fit theory (Vessey 1991) to geographic tasks performed using either map-based presentations or tabular presentations. The experiment found that decision makers using a map-based presentation made faster and more accurate decisions when working on a geographic task in which there were adjacency relationships among the geographic areas. Decision makers using a map-based presentation made faster but less accurate decisions when working on a geographic task in which there were no relationships among the geographic areas.